The Feasibility of Mango Farming Agribusiness in Oro Oro Ombo Wetan Village, Pasuruan Regency - Sri Kusmaryatun; Agnes Quartina Pudjiastuti; Budi Prihatminingtyas (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
Oro-Oro Ombo Wetan Village in Rembang District was an area that produce the highest mango commodity in Pasuruan Regency with a productivity level of 72.95 kg/tree in 2017. The high productivity level didn’t correlate positively with the income. This situation affected by the mango commodity price on the farmer level, investment cost, and production infrastructure cost. The mango production and price in this village relatively fluctuated. Therefore, it important to assess the feasibility and sensitivity of the mango farming agribusiness in this village. This study aimed to know the mango farming agribusiness feasibility in Oro Oro Ombo Wetan Village, Rembang District, Pasuruan Regency, and its sensitivity to the price and production volume change. The survey technique conducted to collect the data. The agribusiness farming feasibility analyzed in the interest level of 8% with the investment criteria of: gross B/C, net B/C, break-even point, payback period, NPV and IRR. The sensitivity analysis used to know the feasibility percentage when the price decrease as much as 10% and the mango production decrease as much as 20%. The result showed that the mango farming agribusiness in Oro-Oro Ombo Wetan village feasible to be conducted. This agribusiness was not sensitive to the decrease of the 10% price and 20% mango volume production.